Influence of feedstock-to-inoculum ratio on performance and microbial community succession during solid-state thermophilic anaerobic co-digestion of pig urine and rice straw. (March 2018) - Meng, Lingyu; Xie, Li; Kinh, Co Thi; Suenaga, Toshikazu; Hori, Tomoyuki; Riya, Shohei; Terada, Akihiko; Hosomi, Masaaki
Highlights: Solid-state batch anaerobic digestion of pig urine and rice straw. A feedstock-to-inoculum ratio (F/I) of 0.5 showed the highest methane yield. No volatile organic acid accumulation in low (0.5) and high (3.0) F/I ratios. Bacterial and archaeal communities were similar between these F/I ratios. Stable operation can be achieved between 0.5 and 3.0 of F/I ratio. Abstract: This study investigated the effect of the feedstock-to-inoculum (F/I) ratio on performance of the solid-state anaerobic co-digestion of pig urine and rice straw inoculated with a solid digestate, and clarified the microbial community succession. A 44-day biochemical methane potential test at F/I ratios of 0.5, 1, 2 and 3 at 55 °C and a 35-day large-scale batch test at F/I ratios of 0.5 and 3 at 55 °C were conducted to investigate the effects of F/I ratio on anaerobic digestibility and analyze microbial community succession, respectively. The highest cumulative methane yield was 353.7 m 3 /t VS in the large-scale batch test. Volatile fatty acids did not accumulate at any F/I ratios. The volatile solids reduction rate was highest at a F/I ratio of 0.5. Microbial community structures were similar between F/I ratios of 3 and 0.5, despite differences in digestion performance, suggesting that stable operation can be achieved at these ratios.